Yesterday, today and tomorrow of credit default swaps. - Hong, LuLu. (2011)
The paper examines on the role of which credit default swaps played in the subprime financial crisis and how it brought about tremendous losses for financial institutions. The discussion focus on the advantages and disadvantages of credit defaults swaps, of how credit default swaps may possibly be manipulated due to the lack of transparency and how risks may arise in the situation when the underlying assets drop in value and big player in CDS business drops out of the market. Lastly we will make an analysis on the new policies and regulations implemented in the market and company to protect themselves from future credit default swaps crisis.